An analysis of plasma reveals proteins in the acute phase response pathway to be candidate diagnostic biomarkers for depression. (February 2019) - Wang, Qi; Yu, Chunyue; Shi, Shanshan; Su, Xiaojie; Zhang, Jian; Ding, Yongqing; Sun, Yanan; Liu, Min; Li, Chunquan; Zhao, Xiwu; Jiang, Wenhai; Wei, Taiming
Highlights: Peripheral plasma protein expression was used to determine clinically relevant biomarkers for depression. This is the first study to observe the up-regulation of CFB and SERPIND1 in plasma from depression. The results indicate that acute phase response signaling pathway dysregulation is associated with depression. Abstract: Globally, depression is one of the most serious debilitating psychiatric mental disorders. In this study, we validated the expression levels of fibrinogen alpha (FGA), fibrinogen beta (FGB), fibrinogen gamma (FGG), Complement factor B (CFB) and serpin family D member 1(SERPIND1) in the acute phase response signaling pathway in plasma samples using enzyme-linked immunosorbent assay (ELISA).Then illuminate the roles of FGA, FGB, FGG, CFB, SERPIND1 in depression using microarray data. Gene expression dataset GSE98793 was downloaded from the Gene Expression Omnibus database. There were 128 whole blood samples included 64 patients with major depressed patients and 64 healthy controls. Differentially expressed genes (DEGs) were identified, and then protein-protein interaction (PPI) network was constructed to screen crucial genes associated with FGA, FGB, FGG, CFB and SERPIND1. Moreover, gene ontology (GO) biological processes analyses was performed. The ELISA data showed that the expression levels of FGA, FGB, FGG, CFB and SERPIND1 were up-regulated in depressed patients. The enriched GO terms were predominantly associated with the biological processes including more genes were inflammation related. The PPI network was found these five genes interacted with 11 genes. FGA, FGB, FGG, CFB and SERPIND1 may be important in the pathogenesis of depression. Graphical abstract: Image, graphical abstract